Limbic Stimulation Drives Mania in STN‐DBS in Parkinson Disease: A Prospective Study. Issue 3 (12th July 2022) - Prange, Stéphane; Lin, Zhengyu; Nourredine, Mikail; Danaila, Teodor; Laurencin, Chloé; Lagha‐Boukbiza, Ouhaid; Anheim, Mathieu; Klinger, Hélène; Longato, Nadine; Phillipps, Clelie; Voirin, Jimmy; Polo, Gustavo; et al.
Abstract : In this one‐year prospective study, Parkinson's disease (PD) patients with or without mania following STN‐DBS were compared to investigate risk and etiological factors, clinical management and consequences. Eighteen (16.2%) out of 111 consecutive PD patients developed mania, of whom 17 were males. No preoperative risk factor was identified. Postoperative mania was related to ventral limbic subthalamic stimulation in 15 (83%) patients, and resolved as stimulation was relocated to the sensorimotor STN, besides discontinuation or reduction of dopamine agonists and use of low‐dose clozapine in 12 patients, while motor and nonmotor outcomes were similar. These findings underpin the prominent role of limbic subthalamic stimulation in postoperative mania. ANN NEUROL 2022;92:411–417